Magnetic resonance imaging-guided transurethral ultrasound ablation in patients with localised prostate cancer: 3-year outcomes of a prospective Phase I study - Nair, Shiva; Hatiboglu, Gencay; Relle, James; Hetou, Khalil; Hafron, Jason; Harle, Christopher; Kassam, Zahra; Staruch, Robert; Burtnyk, Mathieu; Bonekamp, David; Schlemmer, Heinz-Peter; Röthke, Matthias C.; et al. (BJU international, 2021)
Objectives To report the 3-year follow-up of a Phase I study of magnetic resonance imaging (MRI)-guided transurethral ultrasound ablation (TULSA) in 30 men with localised prostate cancer. Favourable 12-month safety and ablation precision were previously described. Patients and Methods As a mandated safety criterion, TULSA was delivered as near whole-gland ablation, applying 3-mm margins sparing 10% of peripheral prostate tissue in 30 men. After 12-month biopsy and MRI, biannual follow-up included prostate-specific antigen (PSA), adverse events (AEs), and functional quality-of-life assessment, with repeat systematic biopsy at 3 years. Results A 3-year follow-up was completed by 22 patients. Between 1 and 3 years, there were no new serious or severe AEs. Urinary and bowel function remained stable. Erectile function recovered by 1 year and was stable at 3 years. The PSA level decreased 95% to a median (interquartile range) nadir of 0.33 (0.1-0.4) ng/mL, stable to 0.8 (0.4-1.6) ng/mL at 3 years. Serial biopsies identified clinically significant disease in 10/29 men (34%) and any cancer in 17/29 (59%). By 3 years, seven men had recurrence (four histological, three biochemical) and had undergone salvage therapy without complications (including six prostatectomies). At 3 years, three of 22 men refused biopsy, and two of the 22 (9%) had clinically significant disease (one new, one persistent). Predictors of salvage therapy requirement included less extensive ablation coverage and higher PSA nadir. Conclusion With 3-year Phase I follow-up, TULSA demonstrates safe and precise ablation for men with localised prostate cancer, providing predictable PSA and biopsy outcomes, without affecting functional abilities or precluding salvage therapy.
Online veröffentlicht: 9. Oktober 2021
Gesehen am 29.07.2024